(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
The measurement and investigation of the ultrasonic velocity (U), density ( ), viscosity ( ), adiabatic compressibility (  a ), intermolecular free length (Lf), Gibb’s free energy (G), molecular volume (Vm), available volume (Va), free volume (Vf) and specific acoustic impedance (Z) studied in binary liquid mixtures of Methyl Propyl Ketone and Bezaldehyde (MPK+C6H5CHO) at 308.15K.